Correlation of Helicobacter Pylori Infection with Acid Peptic Disorders - Thavendra Jaglal Dihare1, Lamture Yashwant R.2, Varsha Gajbhiye3, Gode Dilip4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Introduction: The acid peptic disorder is a disorder in which due to hyperacidity, there is the damage ofinner lining (mucosa) of the stomach and duodenum causing various manifestations like inflammation,ulcer, etc. The acid peptic disorder is a disorder in which due to hyperacidity, there is the damage of innerlining (mucosa) of the stomach and duodenum causing various manifestations like inflammation, ulcer, etc.A major symptom of the acid peptic disorder is a pain in the abdomen typically non radiating, burning, andlocated at in epigastrium, Other include nausea, vomiting, dyspepsia, haemtemesis, and melena, etc. Uppergastrointestinal tract disorders are common in surgical practice. Helicobacter pylori is a common cause ofacid peptic disorders. Still in literature there is a controversy still exist to question about role of Helicobacterin causing acid peptic disorders. So This study was undertaken to evaluate the correlation of H. Pyloriinfection with acid peptic disorders. Method: This study was a prospective observational. The durationof this study was from September 2017 to September 2019. The numbers of patients were 150. After theestablishment of a clinical diagnosis of an acid peptic disorder, the patient was posted for endoscopy. H.pylori status was determined by the rapid urease test. The data collected included the presenting complaints,clinical signs, endoscopic findings, results of rapid urease test, and histopathological examination. Thepresence of H pylori infection was correlated with symptoms, and endoscopy findings. Results: In the presentstudy, 150 patients with upper gastrointestinal symptoms were studied It was found that the maximumnumber of subjects belonged to the age group 31-40 yrs. It was found that of subjects male 112 and female.It was found that maximum number of subjects had pain in epigastric region 120 cases i. e. 80% followedby symptoms nausea 75 cases ie. 50%. about endoscopic findings .70 patients were having gastritis,15 hada duodenal ulcer,9 patients had Duodenitis, the gastric ulcer was found in 08 patients, gastric malignancyin 02 patients and 46 patients had endoscopic normal mucosa. The highest positivity of RUT was seen inpatients of duodenal ulcers (86.66%), followed by gastritis (82.85%) and gastric ulcer (75%). Conclusions:Present study, we have found that there is an association of H. Pylori infection in an acid peptic disorder likeduodenal ulcer, gastric ulcer, and gastritis.